Perpetual Dilemma - Garber, Zev (2016)
My reasons for engaging in a scholarly discussion of the beliefs and practices of Messianic Judaism are straightforward and transforming: to learn what they teach before responding with approval and/or disapproval, recognize differences in religious sancta, and express acceptance or non-acceptance in a nonpolemical and respectful way. As a practicing Jew who dialogues with Christians, I have learned to respect the covenantal role that Gentile Christians understand to be the way of the scriptural Jesus in their confessional lives. But I have serious difficulty in applying the same criteria to affirmed Jewish believers in Torah and Christ Jesus. Why so? They are not Gentiles but they are Trinitarians not Unitarians in their acceptance of ישוע המשיח, Jesus the Messiah—a serious ethnic Jewish (religious) problem which appears unresolvable until ימי משיח, the days of the Messiah.